Student Extraneous Load Analysis in Online-Based Plant Tissue Structure Learning - Ermayanti Ermayanti; Rahmi Susanti; Lucia Maria Santoso; Siti Huzaifah; Chelsea Novalin Deluciana (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the cognitive load of students in online-based plant anatomy learning. The research was conducted at the Biology Education Study Program at a State University in Palembang, Indonesia. The research subjects were Biology Education students (n=73) who contracted the plant anatomy course. The instrument used to determine students' mental effort in understanding plant anatomy material is a questionnaire with a Likert scale with five answer choices: very easy (VE), easy (E), moderate (Md), difficult (D), and very difficult (VD). The aspects measured are (i) identifying the type of tissues and its characteristics by observing 2D and 3D images; (ii) analyzing the interrelationship of tissues structure and it function; (iii) identifying the structure of the constituent tissues in several plant organs, and (iv) spatial thinking related to the structure of plant tissues. The research data shows that the highest percentage in all aspects is in the medium category (MD), which ranges between (31.14% - 47.69%), which means that the learning carried out is not too burdensome for students in these four aspects. However, the data also shows that in the second aspect, namely the ability to analyze the relationship between structure and function, 31.64% of students stated that it was difficult. This is due to the complexity of the material related to the structure and function and the ineffectiveness of the media used in online-based learning